2000
DOI: 10.1093/bja/85.4.577
|View full text |Cite
|
Sign up to set email alerts
|

Static versus dynamic respiratory mechanics for setting the ventilator

Abstract: The lower inflection point (LIP) of the inspiratory limb of a static pressure-volume (PV) loop is assumed to indicate the pressure at which most lung units are recruited. The LIP is determined by a static manoeuvre with a PV-history that is different from the PV-history of the actual ventilation. In nine surfactant-deficient piglets, information to allow setting PEEP and VT was obtained, both from the PV-curve and also during ongoing ventilation from the dynamic compliance relationship. According to LIP, PEEP … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
15
0
1

Year Published

2009
2009
2021
2021

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 29 publications
(16 citation statements)
references
References 29 publications
0
15
0
1
Order By: Relevance
“…Differences in global lung mechanics during static or quasi-static and dynamic ventilatory conditions have long been known (27). It has recently been shown that lung mechanics assessed during continuous ventilationarehelpfulinadjustingindividual ventilatory settings (2,4,(42)(43)(44)(45). As assessment of dynamic lung mechanics does not require invasive interventions and allows continuous assessment of ventilatory settings, they may be of clinical interest.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Differences in global lung mechanics during static or quasi-static and dynamic ventilatory conditions have long been known (27). It has recently been shown that lung mechanics assessed during continuous ventilationarehelpfulinadjustingindividual ventilatory settings (2,4,(42)(43)(44)(45). As assessment of dynamic lung mechanics does not require invasive interventions and allows continuous assessment of ventilatory settings, they may be of clinical interest.…”
Section: Discussionmentioning
confidence: 99%
“…T he pressure/volume relationship of the respiratory system is commonly used to adjust ventilatory variables (e.g., positive end-expiratory pressure [PEEP]) during mechanical ventilation (1)(2)(3). Specifically, the static pressure/ volume loop has been used to select ventilatory settings that counteract collapse and overdistension of alveoli.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Traditionally, static pulmonary mechanics has been used to assess lung mechanics [5]. However, recent studies have indicated that the application of dynamic respiratory mechanics in ventilated patients is more appropriate than the use of static lung mechanics [9][10][11]. Therefore, we have proposed the concept of an individualized RM that was defi ned on the basis of dynamic compliance (Cdyn), which is easily obtained from the ventilator as a bedside diagnostic tool [9][10][11].…”
mentioning
confidence: 99%
“…However, recent studies have indicated that the application of dynamic respiratory mechanics in ventilated patients is more appropriate than the use of static lung mechanics [9][10][11]. Therefore, we have proposed the concept of an individualized RM that was defi ned on the basis of dynamic compliance (Cdyn), which is easily obtained from the ventilator as a bedside diagnostic tool [9][10][11].The purpose of the present study was to assess the safety and effi cacy of our individualized RM in patients after cardiac surgery. The primary endpoint of our study was to verify the hemodynamic effects induced by the individualized RM and to evaluate the improvement in oxygenation and Cdyn.…”
mentioning
confidence: 99%